Dynamic Response on Free-Free Beam in Driving Point and Transfer Mobility Measurement under Bending Load - Salim, Mohd Azli; Nordin, Aminurrashid (David Publishing Company, 2011)
This paper aims to present the experimental result obtained from dynamic response on free-free beam in driving point and transfer mobility analysis using impact test method using hammer tips that are steel, plastic and rubber. The 8630C accelerometer and analyzer is used for data logging and for the analysis, the plastic hammer tip is chosen. The analytical and the experimental value then are compared for the free-free beam natural frequency, damping ratio, and stiffness value. As a result, the highest percentage error for natural frequency is approximated to 2.7%, the damping ratio is approximated to 3.115 × 10-3 and the stiffness value gives the major different between the experiment value and theoretical value. Finally, this method can be used to determine the properties of a structure such as natural frequency, mode shapes, damping ration and stiffness, respectively.